2021
DOI: 10.1039/d1cy00245g
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic oxidative CC bond cleavage of aromatic alkenes by a high valency iron-containing perovskite catalyst

Abstract: High valency iron-containing perovskite catalyst BaFeO3–δ could efficiently promote the additive-free oxidative C=C bond cleavage of various aromatic alkenes to the corresponding aldehydes or ketones using O2 as the sole...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
(35 reference statements)
0
14
1
Order By: Relevance
“…This A-site effect was different from those observed for the aerobic oxidation of alkanes and C=C bond cleavage reactions which are promoted only by perovskite oxides containing high valent iron species such as BaFeO 3-δ and SrFeO 3 . [13] Fe 2 O 3 without Asite metal cations was much less effective for the present oxidation than the iron-containing perovskite oxides. Other Fe 3 + /Fe 2 + -containing simple oxides such as Fe 3 O 4 and FeO were also inactive (entries 8-10).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…This A-site effect was different from those observed for the aerobic oxidation of alkanes and C=C bond cleavage reactions which are promoted only by perovskite oxides containing high valent iron species such as BaFeO 3-δ and SrFeO 3 . [13] Fe 2 O 3 without Asite metal cations was much less effective for the present oxidation than the iron-containing perovskite oxides. Other Fe 3 + /Fe 2 + -containing simple oxides such as Fe 3 O 4 and FeO were also inactive (entries 8-10).…”
Section: Resultsmentioning
confidence: 75%
“…Recently, we have reported various perovskite nanoparticle catalysts for liquid-phase selective oxidation of various organic compounds with O 2 as the sole oxidant. [11][12][13] Among them, we found that the Fe-containing hexagonal perovskite oxide, BaFeO 3-δ , acts as an effective heterogeneous catalyst in aerobic oxidation of alkanes and oxidative C=C bond cleavage reactions of alkenes. [12,13] Herein, we applied the Fe-containing perovskite oxide-catalyzed system to the synthesis of phenacyl bromide from α-bromostyrene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers turned to use hydrogen peroxide (H 2 O 2 ) as an oxidant for this reaction [10][11][12] as H 2 O 2 is environmentally benign and produces water as the only by-product. Some transition metal containing catalysts, [13][14][15][16] such as H 2 WO 4 @Al-MCM-41, 12 BaFeO 3Àd , 17,18 Ru(OH) x /g-Al 2 O 3 19 and VO@TiO 2 20 have been proved efficient in catalyzing this reaction with H 2 O 2 as oxidant. Among them, tungsten containing catalysts such as tungsten oxide (WO 3 ), WO 3 nanoparticles, 24 tungstic acid, 25 tungstates and supported WO 3 [26][27][28][29][30] have shown the best catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed in the oxygenation of CC bonds with O 2 or air as the sole oxidant. However, most of these developed oxidation systems could only chemoselectively transform into the corresponding alcohols, , aldehydes, or ketones, possibly due to the triplet-ground-state of O 2 , which generates a high kinetic barrier to oxidation and results in inefficient utilization of oxygen. , To overcome these drawbacks, several approaches have been reported, such as photocatalyst-promoted, transition-metal catalyzed, and additive-promoted oxidation of alkenes to carboxylic acids using O 2 as the oxygen source. For example, Hirashima et al developed a method for the CBr 4 -catalyzed oxidative cleavage of alkenes to produce carboxylic acids with O 2 under aerobic photoirradiation conditions (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%